Nourishing neonatal piglets with synthetic milk and Lactobacillus sp. at birth highly modifies the gut microbial communities at the post-weaning stage - Sampath, Vetriselvi; Song, Jun Ho; Jeong, Jinuk; Mun, Seyoung; Han, Kyudong; Kim, In Ho (Frontiers in Microbiology, 2022)
The importance of probiotics in pig production is widely recognized. However, the precise role of probiotics in regulating the gut microbiota of piglets has not been assessed extensively. Thus, we intend to examine whether suckling pigs ingest synthetic milk (SM) with probiotic supplementation at early weaning has a carry-over effect on its growth and gut health at the post-weaning stage. A total of forty healthy crossbred [Duroc× (Yorkshire× Landrace)] neonates with an initial BW of 1.49 ± 0.28 kg, were randomly assigned to one of two treatments groups i.e. CON and Treatment (TRT). Control group piglets were nourished with SM while, TRT group piglets were nourished SM with 0.1% Lactobacillus spp. Treatment group piglets showed higher (p<0.05) body weight and daily gain at week 3 compared to the CON group. As a result of 16S metagenome sequencing, the average demultiplexed reads and denoised reads count 157,399 and 74,945 were observed. The total ASVs taxonomy number classified with > 70% (default) confidence threshold about the sequence alignment with the SILVA v138 reference database was 4,474. During week 1, the Escherichia-Shigella, Clostridium sensu stricto 1, and Bacteroides were confirmed as the major dominant bacterial genera at the genus level, in both groups. However, during week 2, the relative proportion of Escherichia-Shigella, Clostridium sensu stricto 1, and Proteobacteria was decreased while, the Lactobacillus and Bacteroidota were increased in pigs receiving the probiotic supplement. Also, the Firmicutes, Proteobacteria, and Bacteroidota phyla were dominant in both comparison groups at weeks 2 and 3. Whereas, at week 6, the Proteobacteria slightly increased relative proportion. Also, the Prevotella was confirmed as the major dominant bacterial genus in both groups in week 3 and 6. Nourishing SM with 0.1% probiotic from birth to 21 days has highly supported the piglets to improve their gut health during post-weaning stage.